تقويم كفايات تخطيط الدروس لدى معلمي اللغة العربية في المرحلة الثانوية بالمدارس العربية في مالي - Muhamad Zaid, Ismail; Nashaat Abdelaziz, Abdelqader Baioumy (2018)
This study sought to reveal the degree of competency lesson planning among Arabic language teachers in Arabic Secondary Schools in Mali, And to determine whether there were statistically significant differences at the level of )α≤0,05( in the grades of their lesson planning due to the variable type of academic qualification. The researchers employed descriptive survey approach to achieve the stated objectives Questionnaire was administered to (143) Arabic language teachers in Mali Arabic secondary schools. The results showed that the degree of lesson planning among the study community in the introductory field, educational content, Behavioral Objectives, and educational activities, respectively, Great degree, Their arithmetic averages ranged between (4,07-3,57). While the study found that the degree of planning their lessons in the areas of teaching strategies and teaching methods, and assessment strategies are medium, ranging in the arithmetic mean between (2,78-2,77), The study revealed the existence of statistically significant differences between the grades of their lesson planning due to the variable of the type of academic qualification in all fields of study to the field of evaluation strategies for the benefit of educators. the study concluded with a number of recommendations and proposals.